THE ENHANCING PRODUCTIVITY AND COMPETITIVENESS OF RURAL MSMES THROUGH APPROPRIATE TECHNOLOGY: INSIGHTS FROM A FOOTWEAR PRODUCER IN EAST JAVA - Hidayati, Cholis; Narastri, Maulidah; Amiranto, Johannes Bambang (International Conference On Economics Business Management And Accounting (ICOEMA), 2025)
Micro, Small, and Medium Enterprises (MSMEs) play a vital role in driving local economic development, especially in rural areas. However, many MSMEs face persistent challenges related to limited production capacity and low competitiveness, largely due to inadequate technological adoption. This study presents insights from a community service initiative aimed at improving the production process of Vario Shoes Lady, a women-led MSME in Junwangi Village, Sidoarjo, East Java. The intervention introduced appropriate production technology, such as semi-automatic sewing machines and ergonomic cutting tools, tailored to the enterprise’s operational needs. Through a participatory approach involving training and mentoring, the intervention succeeded in enhancing production efficiency, reducing defects, and shortening processing time. The findings highlight the significant role of appropriate technology in increasing MSME competitiveness and suggest that localized, context-sensitive technological strategies can be an effective pathway for stimulating rural economic development. This case reinforces the importance of synergizing academic engagement, local wisdom, and technological solutions to empower MSMEs as a backbone of inclusive economic growth.